Zur Bewertung von Wetterderivaten als innovative Risikomanagementinstrumente in der Landwirtschaft - Oliver Mußhoff; Martin Odening; Wie Xu (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2005)
– The importance of weather as a production factor in agriculture is well established long time and a significant portion of yield fluctuations is caused by weather risks. Traditionally, farmers have tried to hedge against unfavorable weather using insurance, such as crop insurance. In recent years a new class of instruments, so called weather derivatives, have emerged. They allows to reduce weather based risks as well. Weather derivatives are financial market products such as forwards, futures, options and swaps, that have a weather component such as temperature or rainfall. Although weather derivatives have some advantages compared to traditional insurance, their trading volume is still rather small. One reason (among others) for why potential users hesitate to enter the market are the difficulties to determine a fair price for these products. Financial pricing methods such as the Black-Scholes formula cannot be directly applied since weather is not a tradable asset. In this article, various pricing methods are investigated and applied to actual weather data. One important finding is that there are considerable differences between the pricing methods. We identify the strengths and weaknesses of the pricing methods and give some recommendations for their application. Our results may be relevant not only for producers but also for potential sellers of weather derivatives.
Keywords: 330; Derivat; Risikomanagement; Optionspreistheorie; Versicherungsmathematik; Wetter